A portable gas recirculation unit for gaseous detectors. (5th October 2017) - Guida, R.; Mandelli, B.
Abstract: The use of greenhouse gases (usually C_2 2 H_2 2 F_4 4, CF_4 4 and SF_6 6 ) is sometimes necessary to achieve the required performance for some gaseous detectors. The consumption of these gases in the LHC systems is reduced by recycling the gas mixture thanks to a complex gas recirculation system. Beyond greenhouse gas consumption due to LHC systems, a considerable contribution is generated by setups used for LHC detector upgrade projects, R&D activities, detector quality assurance or longevity tests. In order to minimise this emission, a new flexible and portable gas recirculation unit has been developed. Thanks to its low price, flexibility and user-friendly operation it can be easily adapted for the different types of detector systems and set-ups.